The Analysis of Conflict Faced by the Main Character in “Spiderman No Way Home” Movie - I Gede Yoga Saputra; Ni Wayan Suastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This research is entitled “The Analysis of Conflict Faced By The Main Character In “Spiderman No Way Home” Movie”. This study aims to find out the types of conflict in Spiderman No Way Home movie and to analyze the conflict management strategies are used by the main character in Spiderman No Way Home movie. In collecting data, this study applied observation method. The method used in analysing the data is a descriptive qualitative method. The writer analysed the data based on the theory types of conflict and conflict management strategies by Kenney (1966). In presenting the findings, formal and informal methods are used. The formal method is used by presenting the data in the form of table to present research findings on the type of conflicts the main character faces, and the informal method is used by explaining the data using description or sentence as well as in the form of text to describe how the main character manages to settle the conflict in the movie through a narrative form. The results showed that the main character of “Spiderman: No Way Home” movie faced two types of conflicts, which were internal conflict and external conflict. The external conflict dominated the data result, with 87.5% over 12.5%. The external conflict happened between the main character with other characters, also with the society. Meanwhile, the internal conflict occurred inside the main character, which was Peter Parker. An analysis of the way the main character manages the conflict was found in “Spiderman: No Way Home” movie, they were compromise, pacification, and competition. Based on the analysis result using Kenney theory (1966), the most strategy found in the movie was competition. It took 90% of the strategy result.